Tibial compression during sustained walking with body borne load. (March 2022) - Walker, Elijah M.; Nelson, Miranda; Drew, Micah D.; Krammer, Samantha M.; Brown, Tyler N.
Abstract: This study determined if sustained walking with body borne load increases tibial compression, and whether increases in tibial compression are related to vertical GRFs. Thirteen participants had tibial compression and vertical GRF measures quantified while walking at 1.3 m/s for 60 min with body borne load. Each tibial compression (maximum and impulse) and GRF measure (peak, impulse, impact peak and loading rate) were submitted to a RM ANOVA to test the main effect and interaction between load ( 0, 15, and 30 kg ) and time ( minute 0, 30 and 60), and correlation analyses determined the relation between tibial compression and vertical GRF measures for each load and time. Each tibial compression and GRF measure increased with the addition of body borne load (all: p < 0.001). Time impacted impact peak (p = 0.034) and loading rate (p = 0.017), but no other GRF or tibial compression measure (p > 0.05). Although both tibial compression and vertical GRFs increased with load, vertical GRF measures exhibited negligible to weak (r: −0.37 to 0.35), and weak to moderate (r: −0.62 to 0.59) relation with maximum and impulse of tibial compression with each body borne load. At each time point, GRF measures exhibited negligible to weak (r: −0.39 to 0.27), and weak to moderate (r: −0.53 to 0.65) relation with maximum and impulse of tibial compression, respectively. Walking with body borne load increased tibial compression, and may place compressive forces on the tibia that lead to stress fracture. But, increases in tibial compression may not stem from concurrent increases in vertical GRFs.